2013
DOI: 10.5402/2013/312706
|View full text |Cite
|
Sign up to set email alerts
|

HPV Prevalence and Detection of Rare HPV Genotypes in Hong Kong Women from Southern China with Cytological Abnormalities

Abstract: Human papillomavirus (HPV) has been identified as the primary cause of cervical squamous intraepithelial lesion and invasive cervical cancer. The emergence of various commercial HPV genotyping kits with different characteristics facilitates the detection of most high-risk and low-risk HPV genotypes, but the rare HPV types are usually underdiagnosed. In the present study, HPV detection was performed using the GenoFlow HPV Array Test kit (DiagCor Bioscience), which can identify 33 HPV subtypes by specific probes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…In this study, HPV 81 was the only genotype detected in a woman with HSIL. High prevalence of HPV 81 was also detected in women with abnormal cytology elsewhere [39,40]. HPV 81 is recognized as a new type mostly found in patients with a weak immune system [40].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In this study, HPV 81 was the only genotype detected in a woman with HSIL. High prevalence of HPV 81 was also detected in women with abnormal cytology elsewhere [39,40]. HPV 81 is recognized as a new type mostly found in patients with a weak immune system [40].…”
Section: Discussionmentioning
confidence: 96%
“…High prevalence of HPV 81 was also detected in women with abnormal cytology elsewhere [39,40]. HPV 81 is recognized as a new type mostly found in patients with a weak immune system [40]. This type is associated with precancerous and cancerous lesions [39].…”
Section: Discussionmentioning
confidence: 97%
“…All the clinical samples were typed during a previous study using RLH as previously described [13]. Briefly, the technique permits the identification of 31 types using specific probes (HPV6, 11,16,18,26,31,33,34,35,39,40,42,44,45,51,52,53,54,55,56,57,58,59, 66, 68, 69, 70, 73, 82, 83, and 84) that were immobilized on a Biodyne C membrane.…”
Section: Hpv Genotypingmentioning
confidence: 99%
“…NGS identified novel LR-HPV (HPV81, HPV43, HPV62 and HPV74) that are considered as rare HPV types [33] and limited studies reported their prevalence. These types were not described so far in Tunisian studies neither in healthy women nor in women with precancerous and cancerous lesions [13,[34][35][36], which further indicates its relevance for epidemiology.…”
Section: Plos Onementioning
confidence: 99%
“…According to Institut Català d’Oncologia and International Agency for Research on Cancer Information Centre on HPV and Cancer (ICO/IARC) report released on 2018, about 917 new cervical cancer cases are diagnosed annually in Iran. Also, cervical cancer ranked as the 16th leading cause of female cancer which accounted as being the 10th most common female cancer in women aged 15–44 years old in Iran [ 10 ]. In line with the Iranian published data, the prevalence of HPV in different female cervical specimens has been reported to be: between 5.5 and 9.4% in normal cytology specimens [ 11 – 13 ]; between 61.7 and 65.3% in Cervical Intraepithelial Neoplasia (I–III) samples [ 12 , 14 , 15 ] and between 75.2 and 87% in cervical cancer specimens with a high heterogeneity among studies [ 16 – 18 ].…”
Section: Introductionmentioning
confidence: 99%